1996
DOI: 10.1074/jbc.271.44.27595
|View full text |Cite
|
Sign up to set email alerts
|

Molten-Globule State of Carbonic Anhydrase Binds to the Chaperone-like α-Crystallin

Abstract: ␣-Crystallin, a multimeric protein, exhibits chaperone-like activity in preventing aggregation of several proteins. We have studied the chaperone-like activity of ␣-crystallin toward heat-induced aggregation of bovine and human carbonic anhydrase. Human carbonic anhydrase aggregates at 60°C, while bovine carbonic anhydrase does not aggregate significantly at this temperature. Removal of the enzyme-bound metal ion, Zn 2؉ , by EDTA modulates the aggregation behavior of bovine carbonic anhydrase. Fluorescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 54 publications
4
65
1
Order By: Relevance
“…␣-lactalbumin (36). In this case, and as with all of the other substrate proteins shown previously to interact with ␣-crystallin (37)(38)(39)(40)(41)(42)(43)(44), the aggregation profile is sigmoidal (Figs. 1a and 2a), indicative of a nucleation-dependent mechanism.…”
Section: Discussionmentioning
confidence: 88%
“…␣-lactalbumin (36). In this case, and as with all of the other substrate proteins shown previously to interact with ␣-crystallin (37)(38)(39)(40)(41)(42)(43)(44), the aggregation profile is sigmoidal (Figs. 1a and 2a), indicative of a nucleation-dependent mechanism.…”
Section: Discussionmentioning
confidence: 88%
“…In nonlenticular tissues, the role of small heat shock proteins may be to maintain substrate proteins in a folding-competent state (15,16). Although the mechanism of the chaperone action of ␣-crystallin is at present not fully understood, it was shown that ␣-crystallin specifically recognizes aggregation-prone nonnative structures that occur early on the denaturation pathway of proteins (17)(18)(19). Furthermore, a number of studies suggest that the chaperone activity of the protein is dependent on the presence of surface-exposed hydrophobic patches (11, 20 -25).…”
mentioning
confidence: 99%
“…Otherwise, they differ in sequence, although there are conserved residues within variable regions that may be essential to their chaperone-like activity (15,19,20). The ATP-independent chaperonelike activity of these proteins is seemingly more directed to preventing protein aggregation early in denaturation, rather than the active refolding of compromised proteins (19,(21)(22)(23)(24)(25). This is an especially important characteristic of the ␣-crystallins, major proteins of the lens which limit aggregation of other eye crystallins and maintain lens transparency (23)(24)(25).…”
mentioning
confidence: 99%
“…The ATP-independent chaperonelike activity of these proteins is seemingly more directed to preventing protein aggregation early in denaturation, rather than the active refolding of compromised proteins (19,(21)(22)(23)(24)(25). This is an especially important characteristic of the ␣-crystallins, major proteins of the lens which limit aggregation of other eye crystallins and maintain lens transparency (23)(24)(25). The ␣-crystallins, and especially ␣B-crystallin, are also found in nonlenticular tissues (26 -28), where their synthesis is induced by stress (24,(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%